Far from home: Genetic variability of Knipowitschia sp. from Italy revealed unexpected species in coastal lagoons of the Tyrrhenian coast. (5th April 2021) - Milana, V.; Šanda, R.; Vukić, J.; Ciccotti, E.; Riccato, F.; Petrosino, G.; Rossi, A.R.
Abstract: Coastal lagoons are resilient and productive ecosystems that support high biological and habitat diversity, but are increasingly affected by several threats due to human exploitation. Many resident species of these environments show a restricted geographical range and a strict association with specific habitats, thus they could represent ecological indicators of these ecosystems. Data on the genetic variability distribution in populations of these species are crucial to identify the presence of different evolutionary units across their geographical distribution ranges and to plan actions for their management and conservation. In this context, the assessment of the genetic variability and structure of Italian specimens of the Adriatic dwarf goby Knipowitschia panizzae, a brackish species endemic in the Adriatic Sea, and included among the species of Community interest in Annex II of Habitats Directive, was carried out. To this purpose, goby samples were collected both from Italian sites where the species is native (Adriatic) and non-native (Tyrrhenian), probably introduced due to the practice of stocking lakes and coastal lagoons with juvenile of euryhaline species to sustain local fisheries. Results show the presence of high values of haplotype diversity, and no shared haplotypes between fish from sites where the species is native or introduced. Moreover, in Tyrrhenian Italian lagoons we identified an allochthonous species of Knipowitschia, previously undetected in Italy: the Corfu dwarf goby K. goerneri . This species was originally described as endemic to the Korission Lagoon catchment on Corfu Island, but recently found also in Butrinti lagoon in Albania. The presence of this species, that almost totally replaced Adriatic dwarf goby in the Tyrrhenian lagoons under study, can be ascribed to the stockings of wild fry of commercially important species originating from Balkan countries. Highlights: Coastal lagoons support high biodiversity and habitats but are increasingly threatened. Genetic data of a species are crucial for conservation actions. Molecular tools represent an easy resource to support classical taxonomy. Non-native species can be translocated by stocking coastal lagoons. Fish introductions might compromise the survival and integrity of local populations.